Variability in and coupling of larval availability and settlement of the mussel Perna perna : a spatio-temporal approach - Porri, Francesca (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2004)
Population dynamics of many intertidal organisms are highly influenced by the abundance and distribution of planktonic larvae in the water column and their arrival on the shore. The brown mussel, Perna perna was used to investigate two of the primary processes that affect population size and dynamics, larval availability and settlement, on the south coast of South Africa. Perna perna is a dominant species on rocky shores of the southern and eastern coasts of South Africa. It creates three-dimensional beds that provide habitats for many other species and hence promotes biodiversity. Larval availability and settlement were examined at different spatial and temporal scales using a nested experimental design. To detect possible relationships between larval availability and settlement, the studies were simultaneous. Two sites, 4km apart, were chosen to investigate mussel settlement patterns. Within each site, three locations (300m from each other) were selected. At each location, five artificial settler collectors were placed at approximately 20cm intervals. Collectors were replaced at a range of time intervals, from daily to seasonal, for 16 months. Each intertidal location was paired with an offshore station, 500m from the shore, where larval availability was measured. At each offshore station, three vertical hauls were collected twice a month using a plankton net. Plankton sampling lasted for 14 months and was designed to examine variability on three temporal scales: seasonal, lunar and daily. The results showed no correlation between the distribution of larvae in the water and settlers on the shore. While larvae were abundant in the water at the start of sampling, they became very rare throughout the rest of the study at both sites and all locations. In contrast, distinct peaks of settler abundance were observed during the seasonal settlement study. In addition to the expected, strong temporal variation that emerged from both studies at all time scales, spatial patterns of variability were also observed. While no spatial effect was detected for the larvae in the water column, there was distinct spatial variation in settlement at the location level: some locations always showed higher settlement than others. These results suggest that, on scales of hundreds of meters to kilometers, larval availability and settlement are very unpredictable in time and that differential delivery of larvae occurs from nearshore waters to the shore. Although the effect of the state of the moon (new or full) was not significant in either study, more settlers seemed to arrive on the shore during new moon. Wind direction did not correlate significantly with settlement. However, the dropping of offshore winds and the prevalence of onshore winds, which are characteristic of summer, may be linked to the start of settlement. Nevertheless, further investigations on tidal or lunar cycles and on the influence of wind on surface currents are required to clarify the effects of moon and wind on settlement.
Keywords: Mussels -- South Africa; Perna -- South Africa; Perna -- Spawning; Perna -- Larvae